2021
DOI: 10.1016/j.intimp.2021.107995
|View full text |Cite
|
Sign up to set email alerts
|

Platelets in the perspective of COVID-19; pathophysiology of thrombocytopenia and its implication as prognostic and therapeutic opportunity

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 153 publications
(171 reference statements)
1
20
2
3
Order By: Relevance
“…Production of autoantibody against PLT glycoproteins also destructs autoantibody-coated PLTs by the reticuloendothelial system leading to thrombocytopenia. 30 A similar findings were reported in Turkey (25.1%), 31 China (17.8%), 32 Iran (30%) 33 and USA (20%). 26 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Production of autoantibody against PLT glycoproteins also destructs autoantibody-coated PLTs by the reticuloendothelial system leading to thrombocytopenia. 30 A similar findings were reported in Turkey (25.1%), 31 China (17.8%), 32 Iran (30%) 33 and USA (20%). 26 …”
Section: Discussionsupporting
confidence: 74%
“…Thrombocytopenia can prolong hospitalization, increase the need of ventilation, and increase patient mortality. 24 …”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients present a wide range of clinical conditions, ranging from asymptomatic infections, minimal symptoms (the majority of patients) to fatal respiratory distress (ARDS) [ 1 ]. Data in published literature have shown that about a quarter of COVID-19 infected patients experienced thrombocytopenia and about half of these patients succumb to infection due to coagulopathy [ 3 , 4 ]. The mechanisms leading to thrombocytopenia are not yet well known.…”
Section: Introductionmentioning
confidence: 99%
“…Among factors not selected in Table 4, several are related to platelet: PLT itself, and MPV and PDW related to platelet size. Because platelet is a key regulator of thrombosis and inflammation, both present in severe COVID-19 patients, it is a good candidate for risk factor (Barrett et al, 2021; Rohlfing et al, 2021; Delshad et al, 2021). However, it is suggested that platelet/large-cell-cell ratio (PLCR) (Daniels et al, 2021) is a better marker than MPV and PDW, and platelet-to-lymphocyte ratio (PLR) (Asan et al, 2021) is a better marker than platelet count.…”
Section: Discussionmentioning
confidence: 99%